PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN NASIONAL - Totok Dewayanto (STIE Pelita Nusantara Semarang, 2010)
Corporate governance remains a major problem during the post-financial crisis period in the growing Asian markets like Indonesia. In particular, financial institutions have adopted corporate governance reforms to improve the protection of the interests of shareholders and stakeholders. Emerged as a consequence allows for greater monitoring, especially by shareholders. The purpose of this study was to measure the corporate governance andperformance in the banking sector which specifically determine a mechanism of corporate governance.Independent variables used in this study is the ownership structure that consists of the ownership of the controlling shareholders, foreign ownership, government ownership, board size, the size of the board of commissioners; independent commissioner; CAR and the external auditors the Big 4. Samples from this study is the general banking company located in Indonesia are listed in Indonesia Stock Exchange (BEI) in the period 2006-2008.This research data come from bank annual reports (annual report) in the period 2006-2008 obtained from the Indonesian Stock Exchange website, the Indonesian Banking Directory, Indonesian Capital Market Directory (ICMD). The analytical method used is multiple linear regression in accordance with the purpose of research which analyzes the influence of independent variables on the dependent variable. Purposive sampling method used to determine the sample selection. From this method, obtained 22 samples of commercial banks.The study shows that direct ownership Monitoring Mechanism relationship is notsignificant to the banking performance. Second, the Internal Control Monitoring Mechanism addressing the significant negative relationship to performance is only one size of banking except that directed the board of directors is a positive but not significant. Third, the Monitoring Mechanism Regulator through and reserve requirements or capital adequacy ratio (CAR) showed significant and positive relationship to performance of the banking system. Fourth